2002
DOI: 10.1016/s0014-5793(02)03187-3
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization, ubiquitylation and endocytosis go together in growth hormone receptor function

Abstract: Internalization of membrane proteins has been studied for more than three decades without solving all the underlying mechanisms. Our knowledge of the clathrin-coated endocytosis is su⁄cient to understand the basic principles. However, more detailed insight is required to recognize why di¡erent proteins enter clathrin-coated pits with di¡erent rates and a⁄n-ities. In addition to clathrin coat components, several adapter systems and even more accessory proteins have been described to preselect membrane proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 104 publications
2
20
0
1
Order By: Relevance
“…Interestingly, unlike many other receptors, internalized GHRs are not recycled back to the surface but are degraded in the lysosomes and are only replaced by newly synthesized receptors (34). This study revealed that SS-14-I significantly increased the internalization of GH.…”
Section: Organismal Growth Integrates a Vast Array Of Biological Procmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, unlike many other receptors, internalized GHRs are not recycled back to the surface but are degraded in the lysosomes and are only replaced by newly synthesized receptors (34). This study revealed that SS-14-I significantly increased the internalization of GH.…”
Section: Organismal Growth Integrates a Vast Array Of Biological Procmentioning
confidence: 71%
“…Such pronounced effects are consistent with downregulation of cell surface GHRs and contributed, at least in part, to the observed reduction of GH binding in the presence of SSs in vivo and in vitro. Two mechanisms for GH internalization have been observed in mammals: a ubiquitin-dependent system appears to modulate internalization of receptor dimers in the presence and absence of ligand, while a ubiquitin-independent system appears to be involved with endocytosis of GHRs not part of a dimer (34). The mechanism(s) by which SS-14 influences GHR internalization and the significance of the presence of two GHRs are not known.…”
Section: Organismal Growth Integrates a Vast Array Of Biological Procmentioning
confidence: 99%
“…Figure 7 summarizes our results and describes the downregulation mechanisms that are turned on by Epo binding to its receptor. In sharp contrast with the GH receptor (GHR), for which internalization is constitutive 16 (and GHR degradation is only slightly increased by GH), 43 internalization and degradation of the EpoR are strongly increased by ligand binding. It has been shown previously that EpoRs unable to bind and activate Jak2 were efficiently internalized after Epo binding, suggesting that Jak2 activation was dispensable for EpoR internalization.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, endocytosis of the receptors is constitutive although their cognate ligands increase to some extent the rate of receptor disappearance. 15,16 Endocytosis of the GH receptor occurs through clathrin-coated pits and depends on an active ubiquitination system and proteasome activity. 17 The internalized receptor is then routed to the lysosome and degraded together with the hormone.…”
Section: Introductionmentioning
confidence: 99%
“…Among frequently asked questions is whether dimerized proteins exist as stable preformed dimers or as dynamic monomeric structures that are modulated by ligands (48)(49)(50)(51)(52)(53)(54). In the case of SR-BI, one can assume the ligand is HDL or one of several other lipoproteins or lipid-associated molecules (6,7,9,55,56).…”
mentioning
confidence: 99%